Securing Endpoint API Integration in Cloud-Based Healthcare Systems: Challenges, Solutions, and Future Directions - Alaa Abas Mohamed (International Journal of Computers and Informatics, 2024)
This paper presents an in-depth analysis of the challenges, solutions, and prospects of endpoint API integration in modern software development, with a specific focus on securing cloud-based healthcare systems. Endpoint API integration plays a crucial role in enabling seamless communication and data exchange between different systems. However, it also presents several challenges that need to be addressed to ensure successful integration and optimal system performance, especially in healthcare. This paper explores the challenges encountered in endpoint API integration, such as security concerns, data inconsistency, lack of standardization, and managing multiple APIs in healthcare environments. It proposes potential solutions, including implementing robust security measures, employing data mapping techniques, adopting API standards, and utilizing API management tools. Additionally, the paper discusses the prospects of endpoint API integration, such as the integration of emerging technologies and continuous improvement in performance, scalability, and security. By addressing these challenges and embracing prospects, healthcare organizations can fully harness the potential of endpoint API integration and drive innovation in their systems.